Additional squat of inland vessels during navigation in navigable channels: Calculation procedures - Škiljaica Ivan V.; Škiljaica Vladimir S.; Živković Mirjana I. (Tehnika)
In the paper, the conditions of movement of displacement-type cargo ships of our shipping companies along waterways were analyzed in order to determine the occurrence of an additional increase in draft of ships, the so-called. additional or dynamic immersion of the ship - ship's squat. The methods applied in the work were the result of foreign research conducted with ships in real navigating conditions as well as special basins, then published in the literature in English and Russian. The author's goal was to, based on the methods published in the paper, examine the phenomenon of additional sinking of ships and determine the influence of ship movement on this phenomenon as a new step in the preparations for searching for the optimal regieme of navigation of ships along these navigable channels. Self-propelled ships for the transport of various types of cargo in channels of variable cross-sectional area and at different navigating speeds were subjected to calculations.